2013
DOI: 10.1111/cmi.12248
|View full text |Cite
|
Sign up to set email alerts
|

Early sequence of events triggered by the interaction ofNeisseria meningitidiswith endothelial cells

Abstract: SummaryNeisseria meningitidis is a bacterium responsible for severe sepsis and meningitis. Following type IV pilus-mediated adhesion to endothelial cells, bacteria proliferating on the cellular surface trigger a potent cellular response that enhances the ability of adhering bacteria to resist the mechanical forces generated by the blood flow. This response is characterized by the formation of numerous 100 nm wide membrane protrusions morphologically related to filopodia. Here, a high-resolution quantitative li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
(59 reference statements)
10
17
0
Order By: Relevance
“…1a), and were enriched in F-actin (Extended Data Fig. 1a), paralleling earlier in vitro studies 11,16,17 . This data shows that the endothelial cell plasma membrane is remodeled during vascular colonization by meningococcus in vivo , supporting the idea of a key role of plasma membrane remodeling in meningococcal pathogenesis, and warranting to further study its underlying mechanisms.…”
Section: Main Textsupporting
confidence: 85%
See 1 more Smart Citation
“…1a), and were enriched in F-actin (Extended Data Fig. 1a), paralleling earlier in vitro studies 11,16,17 . This data shows that the endothelial cell plasma membrane is remodeled during vascular colonization by meningococcus in vivo , supporting the idea of a key role of plasma membrane remodeling in meningococcal pathogenesis, and warranting to further study its underlying mechanisms.…”
Section: Main Textsupporting
confidence: 85%
“…While membrane protrusions are enriched in F-actin 16 , our previous work has shown that inhibition of actin polymerization 11, 16, 17 or depletion of host cell ATP 17 have no effect on the remodeling of the host cell plasma membrane. Bacterial type IV pili (T4P), which are long retractile fibers with a diameter of 6 nm, are required for plasma membrane remodeling in addition to their role in specific adhesion to human cells 12, 17 . Indeed, adhesion of non-piliated bacteria mediated by non-fibrillar adhesins, like Opa, does not lead to the formation of plasma membrane protrusions 19 .…”
Section: Main Textmentioning
confidence: 83%
“…We found that the formation of these clusters requires sufficient concentration of a third partner, Actn4, indicating the necessity of an optimal stoichiometric ratio of receptors and of this cytoskeletal protein. These clusters provide molecular platforms for the elongation of membrane protrusions that were shown to rapidly surround bacteria after their initial adhesion14 and to maintain stable adhesion of growing colonies despite the forces exerted by the blood flow215. In this context, the functional role of these structures would be to provide a sufficient number of binding sites for polymeric bacterial ligands.…”
Section: Discussionmentioning
confidence: 99%
“…β-arrestins then favour the local recruitment and activation of both cytoskeleton-associated and signalling proteins, resulting in remodelling of the apical plasma membrane beneath bacterial colonies1213. Ezrin and moesin, which accumulate within 2–4 min after bacterial contact14, are key players in the reorganization of the cortical actin cytoskeleton at bacterial adhesion sites13. Ultimately, local signalling events result in the formation of membrane protrusions surrounding bacteria and allow them to resist haemodynamic forces15.…”
mentioning
confidence: 99%
“…123 Only a small proportion of these bacteria are able to disseminate from the oropharyngeal cavity to the bloodstream and cross the blood-brain barrier to eventually invade the meninges. 126 N. meningitidis has been observed around the capillaries of the subarachnoidal space, in the brain parenchyma and the choroidal plexuses, and inside brain vessels. 123 Specifically, the adhesion of N. meningitidis to endothelial cells promotes the cleavage of occludin by the metalloproteinase MMP-8.…”
Section: N Meningitidismentioning
confidence: 99%